Electrochemical Detection of Pb(II) Using A Pencil Electrode with Square Wave Anodic Stripping Voltammetry Method - Muhammad Zamhari; Muhamad Aditya Hidayah; Gerda Pintoko Tunjungsari; Endaruji Sedyadi (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
This work describes a simple and inexpensive Pb(II) determination by a pencil electrode using the square wave anodic stripping voltammetry (SWASV) method. This research was applied using a batch cell system on 10 mL of 0.1 M acetate buffer pH 4.5. The precision was performed with repeatability and reproducibility in Pb(II) concentrations of 0.2, 0.4, 0.6, and0.8µg mL-1. Two linear ranges were obtained in the concentration of 0.1–1.0 and 2.0–8.0 µg mL-1. This method offers a detection limit of 0.07 µg mL-1 and a quantification limit of 0.24 µg mL-1. The technique performed good repeatability (RSD= 7.28–9.53%) and good reproducibility (RSD=7.07–15.10%). The precisions are accepted according to the Association of Official Analytical Chemists (AOAC) standard (RSD repeatability <11% and RSD reproducibility <16% at a concentration of 1 µg mL-1). The method offered high operational stability up to 18 measurements (RSD=4.6%). The technique performs acceptable results with low random error in determining Pb(II).